DEVELOPMENT OF VIDEO LEARNING MEDIA IN ENGLISH COURSE AT ISLAMIC RELIGIOUS EDUCATION STUDY, UNIVERSITAS MUHAMMADIYAH GORONTALO - Amara, Basri Usman; Saripi, Samid (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2024)
The development of video learning media for the English course at the Islamic Religious Education Study Program, Universitas Muhammadiyah Gorontalo, aims to enhance the learning experience and improve student engagement. This research explores the design, implementation, and effectiveness of video-based instructional materials tailored to the needs of students in this specific academic context. Using a mixed-methods approach, the study collects data through surveys, interviews, and performance assessments to evaluate the impact of video learning on student comprehension, retention, and satisfaction. Preliminary findings indicate that video learning media significantly contribute to better understanding of course content, increased motivation, and active participation in the learning process. This development not only addresses the challenges of traditional classroom settings but also aligns with contemporary educational trends towards digital learning. The study underscores the importance of integrating multimedia resources in higher education to foster an interactive and dynamic learning environment. Future research will focus on refining the content and exploring long-term effects on academic performance.